An expansion of the q-binomial identities with applications - Wang, Mingjin, (Utilitas Mathematica, 2012)
In this paper, we use the q-exponential operator techniques to give an expansion of the q-binomial identities. As applications of the expansion, we derive some new identities and theorems on the convergence of the q-series with r+1φr..